POESIA PARA SER DITA EM VOZ ALTA: UMA PROPOSTA DE LETRAMENTO COM SLAMS DE AUTORIA FEMININA - SANT ANTONIO, ELAINE (2021)
This work comprises a proposal for pedagogical practice that has the general objective of contributing to the promotion of literary literacy. The anthology Querem nos calar – Poemas para serem lidos em voz alta will support the mediation proposal. Organized by Mel Duarte (2019), this anthology brings out the power and representativeness of the voices of 15 poets from different regions of the country. The intersectionality is understood in the work from the different levels, structures and forms of oppression identified in the experiences of female lyrical voices. Thus, this approach proves to be a powerful form of mediation, in order to understand its plausibility and importance for the emergence of a feminist epistemology that is very useful for understanding the poetry of female authorship that we intend to take to the classroom. For this purpose, we will rely on the contributions of Akotirene (2018), Crenshaw (1989; 2002). We support the discussion on literacy and think literature as a transformative element in the assumptions of Candido (1995; 2002; 2006), Cosson (2014), Dalvi (2013), Soares (1998), Souza (2011) and Zappone (2008) as a basis. The studies by D’alva (2011, 2019), Alves (2007; 2012) and Zumthor (2007) support the questions about poetry, spoken poetry and performance. For the development of the activity nobook, we will use the concept of basic sequence Cosson (2014) as a basis. In terms of results, we hope to contribute to actions in which the development of the ability to use language effectively in the face of comprehension and production of texts is present. In addition to this, actions that mobilize thinking of the school /classroom as a living, flexible and democratic organism for poetry, activating its: aesthetic, humanizing and social functions.